Arcane Society : Sizzle and Burn - Book 3 - Krentz, Jayne Ann (New York : G.P. Putnam's Sons, 2008)
Raine Tallentyre travels to Washington to clean out her deceased aunts house, and her highly developed sensitivity leads her to discover a young woman bound in a storage locker in the basement. Investigator Zack Jones soon arrives on the scene, and an instant intimacy is realized. But Zack works for the Arcane Society, who had betrayed Raines family long ago, and even though a killer is on the loose and targeting her, can Raine trust him?
Keywords: Arcane Society (Imaginary organization) -- Fiction; Aunts -- Death; Fiction; Psychic ability -- Fiction; Secret societies -- Fiction; Washington (State) -- Fiction; Thrillers (Fiction); Romance fiction